A identidade discursiva como elo entre ética e política em Habermas - Sousa, José Rogério Gomes de (2018)
The main purpose of this dissertation is to research the Habermasian perspective trough a theoretical cutout: a decision making in the political sphere is anchored into a lifeworld and communicative action, which enables the formation of an identity. In order to sustain such hypothesis, foremost, it would have to contextualize the paradigm shift effected by Habermas. That is, about how it was given, in modernity, the transition from the paradigm of reason to the paradigm of language. The first paradigm is thought from Descartes and Kant, in which reason is founded on certainties. The second paradigm is approached from the Habermas refusal to such paradigm without falling into a common place of a new rejection of the tradition. In Habermas's understanding, a purely rationalist paradigm would not have the possibility of developing the philosophy given its attention in the subject-object relationship. The pragmatic turn in Jürgen Habermas, displacing the focus to language, understanding as a medium between the relationships of lifeworld. After approaching the importance of language, the lifeworld and communicative action, it could engage into the formation of the medium personality both by the language and by the communicative action that occurs in the lifeworld. The personality´s formation is given through the intersubjective interaction mediated by the language. Such personality is oriented into the pursuit of a mutual understanding. The same is also oriented towards an ethics of discourse, that is, the subject has the ability to judge and criticize ethical norms, and also to raise pretensions of validity. By making such an approach to the identity and its relationship with the ethics of the discourse, it is explained that such formation of the personality of the subject also is relating to the political environment. Thus, through mutual understanding, the individual is able to form consensus in the political sphere. The decisions-making are not unilaterally effected, but is needed the reasons why are deciding on something that will affect the others. That way, the individual must argue about his reasons. Therefore, the lifeworld is where all the social interactions take place that are mediated by the language that enables the formation of identity of the individual who seeks mutual understanding and raises pretensions of validity in both the ethical field and the politics field.